The Problems of Learning Arabic at Madrasah Ibtidayyah - Norhidayah Norhidayah; Aulia Mustika Ilmiani; Nor Anisa Siska; Nurlaila (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
The purpose of this study is to analyze the problems of learning Arabic in class I madrasah ibtidayyah students at the integrated madrasah ibtidayyah "Blessing". This study uses qualitative research that discusses the problems of learning Arabic at Madrasah Ibtidaiyah. As for the type of research used is descriptive qualitative research. The subjects in this study were the students of the integrated Madrasah Ibtidaiyah "Blessing" totaling 36 people. In this study, data collection was carried out by means of observation, interviews, and documentation. As for the data analysis technique used, namely the inductive qualitative analysis method, which was carried out before entering the field, during the field and after finishing in the field. The results of this study indicate that; The problems of Arabic learning faced by first grade students at the integrated Madrasah Ibtidayyah "Blessings" are: (1) Students lack the will to learn Arabic, (2) Environmental backgrounds that do not support the progress of Arabic learning achievement, (3) Students lack confidence in Arabic (4) students do not know the hijaiyyah letters (5) students do not understand Arabic reading.